Protective effect of magnolol on oxaliplatin‐induced intestinal injury in mice. (13th March 2019) - Xia, Ting; Zhang, Jingze; Han, Liying; Jin, Zhaoxiang; Wang, Juan; Li, Xia; Man, Shuli; Liu, Changxiao; Gao, Wenyuan
Abstract : Oxaliplatin (OXL) is the first line treatment therapy for gastrointestinal (GI) cancers and often combines with other chemotherapy. However, few reports have studied on its GI toxicity. Magnolol (MG), one of the mainly active constituents in Magnolia, has been reported to treat digestive diseases. Therefore, the purpose of this study is to evaluate the intestinal protective effect of MG in OXL treatment group. OXL administration mice showed body weight loss, diarrhea, and intestinal damage characterized by the shortening of villi and destruction of intestinal crypts, as well as the colon length change. MG significantly reduced body weight loss, alleviated diarrhea, reversed histopathological changes, and prevented colon length reduction. Oxidative stress and inflammation were activated after OXL, and these responses were repressed by MG through increasing the activities of superoxide dismutase, glutathione peroxidase, and glutathione, decreasing level of nuclear factor of kappa b and downregulating the following pro‐inflammatory cytokines. Although the expression of tight junction protein occludin and numbers of proliferative crypt cells were reduced on ileum and colon after OXL, MG administration promoted these expressions. The fecal gut microbiota composition disturbed by OXL was significantly reversed by MG. Thus, MG could prevent the development and progression of mucositis induced by oxaliplatin through multipathway.